A brief hot‐water treatment alleviates chilling injury symptoms in fresh tomatoes. (1st October 2020) - Loayza, Francisco E; Brecht, Jeffrey K; Simonne, Amarat H; Plotto, Anne; Baldwin, Elizabeth A; Bai, Jinhe; Lon‐Kan, Elena
Abstract: BACKGROUND: Reducing the negative effects of chilling injury (CI) in tomatoes after harvest is essential to ensure good quality and to minimize losses. CI is a postharvest disorder associated with the generation of reactive oxygen species (ROS) in the fruit. Therefore, antioxidant accumulation can counteract ROS, alleviating CI symptoms. In this sense, it has been confirmed that a brief hot‐water (HW) immersion promotes the synthesis of antioxidants. RESULTS: HW treatment at 52 °C for 5 min significantly reduced chilling‐associated decay, from 66.7% to 17.2% in breaker turning (BT) and from 55.8% to 9.8% in mature green (MG) 'BHN‐602' tomatoes stored at 5 °C for 2 weeks and from 26.7% to 6.7% in BT tomatoes stored at 5 °C for 1 week. Also, HW treatment significantly increased lycopene content by 17% in BT tomatoes stored at 5 °C for 2 weeks, as well as ascorbic acid by 11%, lipophilic phenolics by 18% and total phenolics by 6.5% in BT tomatoes stored at 12.5 °C for 1 week. Despite the increase of antioxidants, HW treatment did not enhance the sensory aromatic profile, color and antioxidant capacity. Interestingly, HW treatment reduced ripening time by 3 days in MG tomatoes stored at 5 °C for 2 weeks or at 12.5 °C for 1 week. CONCLUSION: HW treatment applied to MG or BT 'BHN‐602' tomatoes can alleviate the development of some CI symptoms, particularly decay, possibly by increasing antioxidants that scavenge ROS. © 2020 Society of Chemical Industry